Strategi pengendalian mutu program pendidikan nonformal dan informal pada saat pandemic covid-19 - Hidayati, Lilik (Universitas Sebelas Maret, 2020)
The purpose of this study was to determine the quality control strategy for non formal and informal education programs during the Covid-19 pandemic. This study uses acase study to determine the quality control strategy for non-formal and informal education programs during the Covid-19 pandemic. The data in this study were taken from focus group discussions with open-ended question guidelines and related documents. Data were analyzed descriptively. Based on these results it can be concluded that the quality control program is a requirement so that products in the form of goods and services produced by educational institutions can be accepted by customers. As civil servants who have functional positions with the main task of carrying out quality control activities and evaluating the impact of the PNFI program, supportive knowledge and skills are needed, so that what is expected in the draft Permenpan and bureaucratic reform can run and does not happen as indicated by some people that Oversight is a